Covenantal Pluralism in “Homogenous” Japan: Finding a Space for Religious Pluralism - Larsson, Ernils (The review of faith & international affairs, 2022)
This article explores the concept of covenantal pluralism in a context of postwar Japan, with a focus on the legal framework separating the state from religion and guaranteeing the rights of religious minorities. The article argues that while there are relatively few instances of sectarian strife, the lack of agreement on how to interpret the category of religion, in particular in relation to Shrine Shinto, continues to lead to struggles between different camps. The article also questions the feasibility of covenantal pluralism as an ideal in a country where national identity is so closely linked to ideas of social homogeneity.